The Correlation Between Parents' Role Towards Students' Motivation in Learning English in Mentawai - Taileleu, Norlina; Melvina, Melvina; Sevrika, Hevriani (Politeknik Negeri Padang, 2024)
This study aims to determine whether there was a relationship between the role of parents on students' motivation to learn English. This research was conducted using quantitative methods. In one class there were 31 students including parents as the research sample. The research instrument used was a questionnaire. The data analysis technique used in this study was SPSS 29 descriptive data analysis technique. The results showed that the role of parents on students' motivation to learn English reached 55.87%. It can be concluded that the role of parents waas very influential on students' learning motivation in learning English. the results of students' motivation to learn English amounted to 79.129%. This show that some children were motivated to learn English because of their liking and interest in learning English despite the lack of parental involvement in their children's English learning. So it can be concluded that parents should pay more attention to children in terms of education.